Sub-Saharan African Students’ Experiences, Perceptions, and Expectations with American Health Services: An Intercultural Challenge - Claudia L. McCalman; Carol M. Madere (Interpersona: An International Journal on Personal Relationships, 2009)
Understanding patients‟ cultural expectations could contribute to better health outcomes and decrease cultural health disparities. This qualitative pilot study objective was to explore experiences, perceptions, and expectations of males and females Angolan students as patients in America. Eighteen face-to-face interviews were conducted at a Midwestern university. Burgoon‟s expectancy violation theory (1991) was the theoretical background. Results revealed as positive expectation violations an advanced technology, quality of services, medicine availability, and emphasis on preventive care. Negative expectation violations included high service costs, complicated insurance system, short medical encounters, and difficulty in building relational history with providers. The study also revealed that culturally related communication barriers as well as negative violations of expectations hinder the quality of intercultural clinical encounters and can affect health outcomes. Participants emphasized the importance of these interpersonal relations and their connection with perceptions of caregivers‟ professional competence. International patients/students revealed that they believe friendliness on the part of the caregiver is a signal that they are dealing with a “good” doctor or nurse. Intercultural competence is an important asset of caregivers who work in multicultural clinics and in college health. Practical implications emerged in international advising and clinician‟s education.